Criminal liability for crimes related to the illegal conduct of a medical experiment (Diametros, 2023)
In 2021, there was a significant amendment to the legislation on medical experimentation. In particular, Chapter 4 of the Law of December 5, 1996 on the Profession of Physician and Dentist (Journal of Laws 2023, item 1516) was amended, in which the prerequisites of legally relevant consent given by the participant in the experiment or by other entities that express a position on their behalf were specified. In addition, procedures related to the opinion of the research project by the so-called bioethics committee were described. Its members were obliged to maintain confidentiality with regard to information obtained in connection with the fulfilled function. These norms became protected by criminal sanctions, set forth in the amended Article 58 of the law. New generic types of criminal acts were introduced, primarily aimed at protecting the participant's right to self-determination, the voluntariness of participation in the experiment, and the confidentiality of data submitted by the experimenters in their proposals to bioethics committees. These norms fill in the gaps that have existed so far in the criminal law protection of these values. The article systematically discusses the generic types of criminal acts that have been penalized in Article 58 (4) to (6) of the referenced law. Their object of protection, object side, subject, subject side, punishability and potential confluence with other regulations are presented. The historical-dogmatic justification for the introduction of these regulations is also shown.
Keywords: medical experiment; participant’s consent; criminal liability of experimenter; disclosure of secrets; biomedical commission